Implementing Lean Six Sigma into curriculum design and delivery – a case study in higher education. Issue 5 (12th June 2017) - Thomas, Andrew; Antony, Jiju; Haven-Tang, Claire; Francis, Mark; Fisher, Ron
Abstract : Purpose: The purpose of this paper is to propose the development and adoption of a Lean Six Sigma Framework (LSSF) that attempts to create a more balanced and integrated approach between Lean and Six Sigma and one that is capable of achieving improved efficacy of curriculum and programme development in a higher education environment. The implementation of the LSSF is new to the higher education sector. Design/methodology/approach: Using the standard DMAIC cycle as the key driver in the implementation process, most in-depth Lean Six Sigma (LSS) case studies have focussed on manufacturing and engineering-based problems and solutions. This case study offers a detailed analysis of the design and implementation of an integrated LSSF within higher education and focusses primarily on the curriculum design and delivery of a new undergraduate engineering programme in a subject university. As such, this offers a unique perspective of LSS implementation in Higher Education Institutions (HEIs) which drives systems improvements in to the heart of the teaching and learning process. Findings: The design, development and subsequent application of the LSSF enabled the curriculum development team to comprehensively apply LSS in to a subject institution. The Shainin Key Variables Search Technique (KVST) more specifically enabled the team to prioritise the key variables by way of order of importance and, this allowed the team to apply the most appropriate tools and techniques at the key points within the LSSF in order to obtain maximum performance. Research limitations/implications: Whilst this work provides key information on how LSS initiatives are implemented across different institution types, the work has only focussed at a very small sample of HEIs and the case study only being applied to one institution. The work will need to be extended much more widely to incorporate a larger set of HEIs (both research and teaching focussed) in order to provide a more complete map of LSS development in HEIs. Practical implications: The aim of the paper is to provide LSS project leaders in HEIs with a coherent and balanced LSSF in an attempt to assist them in implementing comprehensive LSS programmes thus maximising the improvements in efficiency and operational performance of departments within HEIs. Originality/value: This paper is the first of its kind to study the application of Shainin's KVST in the implementation of LSS programmes in HEIs. The key features highlighted in this work raise important issues regarding the need and importance of developing a balanced LSSF for HEI project implementation.